Some ethical and economic aspects of interest - O'Brien, George (Statistical and Social Inquiry Society of Ireland, 1932)
The suggestion has recently been advanced simultaneously in two very responsible periodicals, the 'Economic Journal' and 'Studies' that modern developments of monetary theory have vindicated the moral teaching of the Catholic Church on interest and usury. Transactions, it is claimed, which would have been condemned as immoral by medieval theologians now stand condemned as noxious from the economic viewpoint as well. This interesting suggestion has involved its proponent in two keenly contested controversies? the controversy, on the one hand, waged among theologians regarding the ethical aspect of interest, and, on the other hand, the controversy between economists regarding the relation between the rate of interest and the value of money. Some aspects of the former controversy have been explained in Studies, and some points arising out of the latter controversy have been discussed by Mr. Keynes and others in the Economic Journal. The object of the present paper is to elucidate the main issues involved in the two controversies, and to indicate in what manner, if at all, they bear on each other, in language intelligible to those who, while interested in the issues involved, do not pretend to any expert knowledge either of moral theology or of modern monetary theory.
Read before the Society on Thursday, 12th May, 1932
Keywords: Usury; Catholic Church; Interest; 314.15